Cardioprotective effects of 5‐hydroxymethylfurfural mediated by inhibition of L‐type Ca2+ currents. (9th September 2017) - Wölkart, G; Schrammel, A; Koyani, C N; Scherübel, S; Zorn‐Pauly, K; Malle, E; Pelzmann, B; Andrä, M; Ortner, A; Mayer, B
Abstract : Background and Purpose: The antioxidant 5‐hydroxymethylfurfural (5‐HMF) exerts documented beneficial effects in several experimental pathologies and is currently tested as an antisickling drug in clinical trials. In the present study, we examined the cardiovascular effects of 5‐HMF and elucidated the mode of action of the drug. Experimental Approach: The cardiovascular effects of 5‐HMF were studied with pre‐contracted porcine coronary arteries and rat isolated normoxic‐perfused hearts. Isolated hearts subjected to ischaemia/reperfusion (I/R) injury were used to test for potential cardioprotective effects of the drug. The effects of 5‐HMF on action potential and L‐type Ca 2+ current (ICa, L ) were studied by patch‐clamping guinea pig isolated ventricular cardiomyocytes. Key Results: 5‐HMF relaxed coronary arteries in a concentration‐dependent manner and exerted negative inotropic, lusitropic and chronotropic effects in rat isolated perfused hearts. On the other hand, 5‐HMF improved recovery of inotropic and lusitropic parameters in isolated hearts subjected to I/R. Patch clamp experiments revealed that 5‐HMF inhibits L‐type Ca 2+ channels. Reduced ICa, L density, shift of ICa, L steady‐state inactivation curves toward negative membrane potentials and slower recovery of ICa, L from inactivation in response to 5‐HMF accounted for the observed cardiovascular effects. Conclusions and Implications: Our data revealed a cardioprotective effect of 5‐HMF in I/R that is mediated by inhibition of L‐type Ca 2+ channels. Thus, 5‐HMF is suggested as a beneficial additive to cardioplegic solutions, but adverse effects and contraindications of Ca 2+ channel blockers have to be considered in therapeutic application of the drug.